KARAKTERISTIK KEJADIAN SOLUSIO PLASENTA DI RSUD PURBALINGGA PERIODE TAHUN 2001 – 2006 - Surtiningsih Surtiningsih (Universitas Harapan Bangsa Purwokerto, 2008)
The purpose of this study was to determine the characteristics of the incidence ofplacental abruption in hospitals Purbalingga the period January 2001 to January,2006.Methods This research is descriptive Retrospective Study. Samples of thisresearch is data mothers who have placental abruption in hospitals Purbalinggain the period January 2001 - January 2006 were taken in total or total population.The results of this study is the number of occurrences of placental abruption inwomen giving birth in hospitals Purbalingga were 19 cases with characteristics ofplacental abruption incidence seen from the respondent's age is> 35 years asmany as 10 people (52.63%) and views of parity is parity> 3 were 13 cases(68.42%).The conclusion in this study that the characteristics of the incidents in hospitalsPurbalingga Placental abruption is the age and parity. Keywords: placental abruption characteristics, age, parity.